Antigen(s) responsible for immunoglobulin G responses specific for the acute stage of Toxoplasma infection in humans. - Suzuki, Y (1988)
An agglutination test for immunoglobulin G (IgG) Toxoplasma antibodies with acetone-fixed tachyzoites (AC antigens; AC agglutination test) was positive only with sera from patients during the acute stage of their infection. In contrast, when the test was performed with Formalin-fixed tachyzoites (HS antigens; HS agglutination test), positive results were obtained during both the acute and chronic (latent) stages of the infection. Studies were performed to define the antigen(s) of T. gondii which are detected by IgG antibodies present only during the acute stage of the infection. Sera of mice immunized with AC antigens recognized predominantly 10 antigens of tachyzoites by immunoblot analysis. Sera from individuals with the acute but not chronic infection reacted strongly with these same 10 antigens in immunoblots. Sera of mice immunized with HS antigens recognized more Toxoplasma antigens on immunoblots than did mouse AC antibodies. Absorption of the latter with HS antigens removed detectable reactivity of AC antibodies in immunoblots and in the AC and HS agglutination tests, suggesting that AC antigens are a selected portion of HS antigens. AC antigens were specific for tachyzoites in that AC antibodies reacted with the cell membranes of both forms of the organism in an indirect fluorescent-antibody test. Tachyzoite-specific antigen(s) appear to be useful in differentiating between the acute and chronic stages of Toxoplasma infection through their detection by IgG antibodies.